Pengaruh Penerapan SIMDA, SAP, Motivasi Pegawai dan Kompetensi SDM Terhadap Kualitas Laporan Keuangan Pada Pemerintah Kabupaten Minahasa Selatan - Runtuwene, Christina; Saerang, David P E; Morasa, Jenny (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. In order to achieve accountability and transparency, local governments are required to develop qualified financial reports. Qualified financial reports are considered as responsibilities of Local Government financial management. They should meet the qualitative characteristics of the financial statements: relevant, reliable, comparable and understandable. Factors that allegedly influence the quality of local government financial reports are the implementation of regional management information system (SIMDA) (X1), government accounting standards (SAP) (X2), employee motivation (X3), and human resources competency (X4). This study aims to examine the influence of implementation of regional management information system (SIMDA), government accounting standards (SAP), employee motivation, and human resources competency to the quality of financial reporting in South Minahasa regency. This is a quantitative research and data were collected by distributing questionnaires. In this study, samples were taken from 102 respondents. They were from 48 regional work unit (SKPD) in South Minahasa regency government. The data were analysed by multiple linear regression, data validity test, data reliability test, and classic assumption test. The data were processed by using Statical Product and Services Solution (SPSS) Software 22 version. The results shows that (1) the implementation of regional management information system (SIMDA) has a positive and significant effect to the quality of financial  report of South Minahasa regency, (2) government accounting standards (SAP) has a positive and significant effect on the quality of financial  report of South Minahasa regency, (3) employee motivation has a positive and significant effect on the quality of financial  report of South Minahasa regency, and (4) human resources competency has a positive and significant effect on the quality of financial  report of South Minahasa regency. Keywords: Implementation of regional management information system (SIMDA), government accounting standards (SAP), employee motivation, human resources competency and quality of financial reportingAbstrak. Dalam rangka mewujudkan akuntabilitas dan transparansi, pemerintah daerah dituntut untuk menyusun laporan keuangan yang berkualitas sebagai bentuk pertanggungjawaban atas pengelolaan keuangan daerah. Laporan keuangan yang berkualitas harus memenuhi karakteristik kualitatif laporan keuangan yaitu: relevan, andal, dapat dibandingkan dan dapat dipahami. Faktor-faktor yang diduga mempengaruhi kualitas laporan keuangan pemerintah daerah adalah penerapan sistem informasi manajemen daerah (SIMDA) (X1), standar akuntansi pemerintahan (SAP) (X2), motivasi pegawai (X3), dan kompetensi SDM (X4). Penelitian ini bertujuan untuk menguji pengaruh penerapan SIMDA, SAP, motivasi pegawai dan kompetensi SDM terhadap kualitas laporan keuangan pada pemerintah Kabupaten Minahasa Selatan. Jenis data yang digunakan pada penelitian ini adalah kuantitatif dan pengumpulan data digunakan kuesioner. Dalam penelitian ini diambil sampel dari 102 responden yang terdapat pada 48 SKPD di pemerintah Kabupaten Minahasa Selatan. Metode analisis data yang digunakan yaitu regresi linier berganda, dengan pengujian validitas data, uji reliabilitas data, uji asumsi klasik, dan analisis regresi berganda. Data diolah dengan menggunakan perangkat Software Statical Product and Services Solution (SPSS) versi 22. Hasil penelitian menunjukkan bahwa (1) penerapan SIMDA berpengaruh positif dan signifikan terhadap kualitas laporan keuangan pemerintah Kabupaten Minahasa Selatan, (2) SAP berpengaruh positif dan signifikan terhadap kualitas laporan keuangan pemerintah Kabupaten Minahasa Selatan, (3) motivasi pegawai berpengaruh positif dan signifikan terhadap kualitas laporan keuangan pemerintah Kabupaten Minahasa Selatan, dan (4) kompetensi SDM berpengaruh positif dan signifikan terhadap kualitas laporan keuangan pemerintah Kabupaten Minahasa Selatan.Kata Kunci: Penerapan SIMDA, SAP, Motivasi Pegawai, Kompetensi SDM Dan Kualitas Laporan Keuangan.